2022
DOI: 10.3389/fcvm.2022.931622
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Markers Indicating Right Ventricular Outflow Tract Conduction Delay as a Predictor of Major Arrhythmic Events in Patients With Brugada Syndrome: A Systematic Review and Meta-Analysis

Abstract: IntroductionRisk stratification in Brugada Syndrome (BrS) patients is still challenging due to the heterogeneity of clinical presentation; thus, some additional risk markers are needed. Several studies investigating the association between RVOT conduction delay sign on electrocardiography (ECG) and major arrhythmic events (MAE) in BrS patients showed inconclusive results. This meta-analysis aims to evaluate the association between RVOT conduction delay signs presented by aVR sign and large S wave in lead I, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In the analyzed group of patients, we observed a higher occurrence of aVR sign in the resting ECG in patients with BrS compared to patients with negative SCBT, expanding the findings of the previous study which reported aVR sign only in BrS patients with spontaneous type 1 BrS ECG pattern [53]. It should be underlined that aVR sign is associated with a worse prognosis (arrhythmic events) in patients with BrS [33,54].…”
Section: Twelve-lead Ecgsupporting
confidence: 84%
“…In the analyzed group of patients, we observed a higher occurrence of aVR sign in the resting ECG in patients with BrS compared to patients with negative SCBT, expanding the findings of the previous study which reported aVR sign only in BrS patients with spontaneous type 1 BrS ECG pattern [53]. It should be underlined that aVR sign is associated with a worse prognosis (arrhythmic events) in patients with BrS [33,54].…”
Section: Twelve-lead Ecgsupporting
confidence: 84%
“…In BrS, conduction delay is associated with accumulation of adipocytes and interstitial fibrosis in the RVOT area, which is seen as a predictor of major arrhythmic events in patients with BrS. 22 It is possible that similar mechanisms exist in Fam-STD, however, additional evidence from e.g. comprehensive histological cardiac examination, advanced mapping and imaging, in vitro modelling, etc.…”
Section: Discussionmentioning
confidence: 99%